Smart Home System Based On The Internet Of Things - Jakbarov, Asliddin (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article studies the architecture, operating principles and implementation methodology of a smart home system based on Internet of Things (IoT) technology. Real-time monitoring and automatic control of temperature, humidity, motion, light and energy consumption were carried out through a prototype system built using Raspberry Pi 4 and Arduino Uno microcontrollers. The experimental results showed that the system reduced lighting costs by 38%, heating and cooling costs by 29%, and total energy consumption by an average of 26%. Based on security analysis, TLS/SSL encryption and two-factor authentication were used. The integration of Zigbee and MQTT protocols significantly increased the stability and energy efficiency of the system. The research results can serve as a practical foundation for the development of smart home technologies in Uzbekistan.